The Regional Economic Value of Entrepreneurship: A Schumpeterian Approach to the Linkage between Entrepreneurship and Regional Development - Sousa, Sonia (Journal of Reviews on Global Economics, 2013)
Abstract: This paper develops a regional-level total factor productivity (TFP)-based proxy measure of the economic value of the functions entrepreneurs perform in the economy. In providing the theoretical support for linking the economic value of entrepreneurship (EVE) and TFP, this paper integrates Schumpeter’s definition of entrepreneurship within the neoclassical production function framework. The measure of EVE developed here builds upon Harberger’s (1998) real cost reduction approach to industry-level and quality-adjusted TFP. The paper uses the European Union NUTS 2 regions as a case study and concludes that this innovative proxy measure of EVE opens promising avenues for a better understanding of the linkages between entrepreneurship and regional economic development.